2021
DOI: 10.1111/cob.12475
|View full text |Cite
|
Sign up to set email alerts
|

Affordability and features of home scales for self‐weighing

Abstract: Summary Self‐weighing is an evidence‐based weight management strategy, which requires patients to have a home scale. For clinicians to effectively counsel patients on self‐weighing, they should be aware of the costs and features available in typical home scales. Our objective was to describe the cost and features of the top bathroom scales available online. We performed content analysis of top 100 scales listed on a popular online retailer. Two coders independently extracted price and scale features (i.e., dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This negatively impacted their ability to monitor their weight in a home/community setting. Studies on access to weighing scales are limited, though it has been reported that most commercial scales have a maximum weight of 150-180 kgs, and that scales with maximum weight above this range were more costly and less common [39]. As weight monitoring can be beneficial to weight management, patients are disadvantaged in this regard due to reduced access to weighing scales [39].…”
Section: Service-related Factors Influencing Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This negatively impacted their ability to monitor their weight in a home/community setting. Studies on access to weighing scales are limited, though it has been reported that most commercial scales have a maximum weight of 150-180 kgs, and that scales with maximum weight above this range were more costly and less common [39]. As weight monitoring can be beneficial to weight management, patients are disadvantaged in this regard due to reduced access to weighing scales [39].…”
Section: Service-related Factors Influencing Transitionmentioning
confidence: 99%
“…Studies on access to weighing scales are limited, though it has been reported that most commercial scales have a maximum weight of 150-180 kgs, and that scales with maximum weight above this range were more costly and less common [39]. As weight monitoring can be beneficial to weight management, patients are disadvantaged in this regard due to reduced access to weighing scales [39]. Lack of access to weighing scales, and social service support needs including specialised equipment, may require the integration and establishment of additional support networks which can be managed/addressed through social work and care coordination as well as from services such as the NDIS, through recognition of the impacts of obesity regarding disability.…”
Section: Service-related Factors Influencing Transitionmentioning
confidence: 99%
“…When a CVAD is placed for a home IVF in patients with SBS, it is recommended to locate the tip of the CVAD in the lower superior vena cava, adjacent to the right atrium, to decrease the risk of catheter‐related venous thrombosis, in case PN is required using the same access 30 . It is also important to monitor weight closely using an affordable home scale to determine if switching the IVF to PN is necessary 32 …”
Section: Use Of Ivfs In Home Settingsmentioning
confidence: 99%